Platelet Metabolism and Other Targeted Drugs; Potential Impact on Immunotherapy - Kanikarla-Marie, Preeti; Lam, Michael; Sorokin, Alexey V.; Overman, Michael J.; Kopetz, Scott; Menter, David G. (Frontiers in Oncology, 2018)
The role of platelets in cancer progression has been well recognized in the field of cancer biology. Emerging studies are elaborating further the additional roles and added extent that platelets play in promoting tumorigenesis. Platelets release factors that support tumor growth and also form heterotypic aggregates with tumor cells, which can provide an immune-evasive advantage. Their most critical role may be the inhibition of immune cell function that can negatively impact the body’s ability in preventing tumor establishment and growth. This review summarizes the importance of platelets in tumor progression, therapeutic response, survival, and finally the notion of immunotherapy modulation being likely to benefit from the inclusion of platelet inhibitors.